Poverty, price and preference barriers to improving diets in sub-Saharan Africa - Headey, Derek D.; Ecker, Olivier; Comstock, Andrew R.; Ruel, Marie T. (Elsevier, 2023)
Suboptimal diets are the most important preventable risk factor for the global burden of non-communicable diseases. The EAT-Lancet reference diet was therefore developed as a benchmark for gauging divergence from healthy eating standards. However, no previous research has comprehensively explored how and why this divergence exists in poorer countries undergoing nutrition transitions. This study therefore analyzes dietary patterns and drivers of the demand for nutritious foods using nationally representative household surveys from Ethiopia, Kenya, Tanzania, and Uganda. We show how barriers to dietary convergence stem from combinations of poverty, high relative food prices and weak preferences for some specific healthy foods. The article concludes by discussing interventions for strengthening consumer demand for healthy diets in Africa.